INVENTORY PLANNING AND CONTROL IN ORGANIZATIONS - Mariano, Dyck Hellington Ataliba; Gomes, Rickardo Léo Ramos (Seven Editora, 2026)
The contemporary organizational context is characterized by high levels of competitiveness, dynamic markets, and increasing complexity in logistical operations, which demand greater efficiency in the management of available resources. In this scenario, inventory planning and control play a fundamental role, as they directly impact operational continuity, cost reduction, and customer service levels. In light of this, the general objective of this study is to highlight the strategic relevance of inventory planning and control within organizations, as well as the main methods and techniques employed and their impacts on organizational performance. To achieve these objectives, a qualitative approach was adopted, grounded in bibliographic research. The study was developed based on the analysis of well-established materials in the literature, such as books and scientific articles by recognized authors in the field of logistics and inventory management, enabling the construction of a consistent theoretical foundation on the topic. The findings indicate that supply management professionals must go beyond the operational mastery of control tools and techniques, developing a strategic perspective that enables the integration of inventory data with managerial decision-making and organizational objectives. Such capability constitutes a significant competitive advantage in the current context, marked by the complexity of supply chains and increasing demands for efficiency and agility in operations.